2003
DOI: 10.1007/s00122-003-1461-3
|View full text |Cite|
|
Sign up to set email alerts
|

A RAPD, AFLP and SSR linkage map, and QTL analysis in European beech (Fagus sylvatica L.)

Abstract: The genetic linkage map of European beech ( Fagus sylvatica L.) that we report here is the first to our knowledge. Based on a total of 312 markers (28 RAPDs, 274 AFLPs, 10 SSRs) scored in 143 individuals from a F(1) full-sib family. Two maps (one for each parent) were constructed according to a "two-way pseudo-testcross" mapping strategy. In the male map 119 markers could be clustered in 11 major groups (971 cM), while in the female map 132 markers were distributed in 12 major linkage groups (844 cM). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 47 publications
2
32
2
3
Order By: Relevance
“…These microsatellites were selected because they showed Mendelian inheritance, a high level of polymorphism (Pastorelli et al, 2003) and because they were unlinked (Scalfi et al, 2004). PCR amplifications were performed following the conditions reported in Pastorelli et al (2003) and fragment size detection was conducted as described by Buiteveld et al (2007).…”
Section: Study Sites Sample Collection and Microsatellite Analysismentioning
confidence: 99%
“…These microsatellites were selected because they showed Mendelian inheritance, a high level of polymorphism (Pastorelli et al, 2003) and because they were unlinked (Scalfi et al, 2004). PCR amplifications were performed following the conditions reported in Pastorelli et al (2003) and fragment size detection was conducted as described by Buiteveld et al (2007).…”
Section: Study Sites Sample Collection and Microsatellite Analysismentioning
confidence: 99%
“…The first QTLs associated with Δ 13 C were reported by Martin et al (1989) in tomato and since that time QTLs for Δ 13 C have been identified in rice (Price et al 2002) and several other plant species (Brendel et al 2002;Casasoli et al 2004;Diab et al 2004;Ellis et al 2002;Gleick 2003;Hausmann et al 2005;Masle et al 2005;Rebetzke et al 2008;Saranga et al 2004;Scalfi et al 2004;Specht et al 2001;Teulat et al 2002;Thumma et al 2001). Until now, all QTL studies conducted in rice involved segregating populations evaluated at different growth stages in field environments.…”
Section: Introductionmentioning
confidence: 99%
“…The same observations were made for the number of leaves and the total dry weight. The instability of QTLs over years has been reported for leaf traits in other tree species (Scalfi et al, 2004;Gailing, 2008;Gailing et al, 2013). Fanizza et al (2005) hypothesized that QTL instability over time may be due to the presence of different genes or the differential expression of these genes due to changes in genotypic sensitivity to annual variations in the climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous QTL studies on main crops have frequently detected regions of the genome that contain clusters of QTLs for highly correlative traits (Zeng et al, 2009;Avia et al, 2013;Bian et al, 2013). Clusters of QTLs were also observed for growth traits and various leaf traits in poplar (Bradshaw and Stettler, 1995;Wu et al, 1997), for wood properties and growth traits in the genus Eucalyptus (Verhaegen et al, 1997;Freeman et al, 2009;Thumma et al, 2010), for growth traits in Salix (Tsarouhas et al, 2002;Ronnberg-Wastljung et al, 2005), for leaf morphological characters in European beech (Scalfi et al, 2004) and oak (Gailing, 2008;Gailing et al, 2013), and for chemical compositions in peach (Eduardo et al, 2013) and oil palm (Montoya et al, 2013). Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation